PROVISION OF READING GARDEN AS A SOLUTION TO INCREASE INTEREST IN READING IN SINDANG MANDI VILLAGE: PENYEDIAAN TAMAN BACA SEBAGAI SOLUSI UNTUK MENINGKATKAN MINAT BACA DI DESA SINDANG MANDI - Rani Puspa; Rizki Najiulloh; Rian Aji Pangestu; Neneng Masitoh; Khaerul Ansori; Lenny Kurniawati; Marissa Rifdayanti; Naziratul Amala; Yufa Wandasari; Dede Yusuf (Yayasan Education and Social Center, 2022)
Reading is something that everyone should do, from children and teenagers to adults and parents, because reading allows them to keep up with all the changes happening in the world. Through reading, people can generate new ideas, obtain information, and increase knowledge, so that their vision becomes wider and develops. However, this reading habit has not been fully realized in developing countries such as Indonesia, especially in Sindang Mandi Village, Anyar. Therefore, the service team carried out this activity as a solution to foster reading interest in Sindang Mandi Village. It is hoped that after this Community Reading Park (TBM) activity, interest in reading in Sindang Mandi will increase